Escape is a more common mechanism than avidity reduction for evasion of CD8+ T cell responses in primary human immunodeficiency virus type 1 infection. - Turnbull, E; Baalwa, J; Conrod, K; Wang, S; Wei, X; Wong, M; Turner, J; Pellegrino, P; Williams, I; Shaw, G; Borrow, P (2011)
BACKGROUND: CD8+ T cells play an important role in control of viral replication during acute and early human immunodeficiency virus type 1 (HIV-1) infection, contributing to containment of the acute viral burst and establishment of the prognostically-important persisting viral load. Understanding mechanisms that impair CD8+ T cell-mediated control of HIV replication in primary infection is thus of importance. This study addressed the relative extent to which HIV-specific T cell responses are impacted by viral mutational escape versus reduction in response avidity during the first year of infection. RESULTS: 18 patients presenting with symptomatic primary HIV-1 infection, most of whom subsequently established moderate-high persisting viral loads, were studied. HIV-specific T cell responses were mapped in each individual and responses to a subset of optimally-defined CD8+ T cell epitopes were followed from acute infection onwards to determine whether they were escaped or declined in avidity over time. During the first year of infection, sequence variation occurred in/around 26/33 epitopes studied (79%). In 82% of cases of intra-epitopic sequence variation, the mutation was confirmed to confer escape, although T cell responses were subsequently expanded to variant sequences in some cases. In contrast, < 10% of responses to index sequence epitopes declined in functional avidity over the same time-frame, and a similar proportion of responses actually exhibited an increase in functional avidity during this period. CONCLUSIONS: Escape appears to constitute a much more important means of viral evasion of CD8+ T cell responses in acute and early HIV infection than decline in functional avidity of epitope-specific T cells. These findings support the design of vaccines to elicit T cell responses that are difficult for the virus to escape.